Delicious eaudiobook - Black, Shayla (Wicked Lovers, 2012)
Luc's entire future is planned out—but there is one very sexy obstacle in his path: Alyssa, a strip club owner with whom Luc recently shared one night of wild abandon. It left Luc terrified by his loss of self—control—and Alyssa desperate for more. But Luc is not the only man desperate to have Alyssa...and that's just one of her secrets—secrets as dark and mysterious and delicious as her fantasies.